NILAI MORAL DAN PENDIDIKAN KARAKTER DALAM FILM “THE PEANUT BUTTER FALCON” - Ita Listiana; Luqman Al Hakim (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2023)
The study aims to analyze the moral value and character education in the movie “ThePeanut Butter Falcon”. The researcher used a qualitative descriptive method. The datacollected by researcher were watching the film, reading the script of film, and notetaking record all data film. The researcher used the validity triangulation data andtriangulation theory to check the validation. The result of the research showed therewere eight moral value that could be found in “The Peanut Butter Falcon” movie suchas honesty, bravery, confidence, peace, dependability, respect, friendship, and mercy.And for character education there were four character educational could be found in“The Peanut Butter Falcon” movie such as hardworking, kindness, loving goodness andresponsibility.Keywords: Moral Value, Character Education, The Peanut Butter Falcon